Pengaruh E-WOM pada Media Sosial Instagram terhadap Minat Beli Jasa Wedding di “We Are The Organizers” Manado - Cambey, Clara Angely; Darwis, Riadi; Widaharthana, I Putu Esa (HeadWay Research & Developemnt, 2024)
The role of social media on the Internet is undisputable nowadays; therefore, all kinds of industries use them to promote their products, including wedding organizers. This research, therefore, aims to examine the effect of Electronic Word of Mouth (E-WOM) on Instagram toward the interest in purchasing wedding services at “We Are The Organizers” Manado. Inferential quantitative methods are used through data collected by documentation and questionnaires. Multiple linear regression analysis was used to test the effect of E-WOM dimensions: Intensity, Valence of Opinion, and Content towards the interest in purchasing the wedding service. The t-test results show that intensity and valence of opinion have a significant positive effect on the interest to purchase, while content does not have a significant effect on the interest to purchase the wedding service at “We Are The Organizer” Manado. The F test shows that these three variables simultaneously have a positive effect on buying interest with a significance value of 0.000. Therefore, it is recommended that “We Are The Organizers” present more detailed information about wedding packages through Instagram social media, as well as provide a direct link to the company's official website to make it easier for potential consumers to access additional information and updates regarding wedding services.